DI-045 Drug stability in peritoneal dialysis solutions. (24th February 2014) - Sennesael, AL; Hecq, JD
Abstract : Background: Since 1978 peritoneal dialysis (PD) has represented an alternative to haemodialysis in end-stage renal disease, offering possibilities of renal replacement treatment at home. Drugs are frequently added to PD solutions in our clinical practice, particularly for the treatment of peritonitis, which remains the principal complication and a cause of mortality. Intraperitoneal administration of drugs is also considered for systemic effects (e.g. insulin, heparin). Nevertheless drug stability in new PD solutions is often unknown. Purpose: To review the literature about drug stability in PD solutions and provide a practical tool for hospital pharmacists. Materials and methods: A Medline search was performed to identify studies about drug stability in PD solutions. The studies were analysed according the following criteria: drug concentration, type of PD solution, nature of recipient, light and temperature conditions, duration. Stability was defined as a maximum of 10% drug degradation. Results: 457 data were collected during the review, findings for23 drugs including 17 antibiotics and 2 antimycotics. 306 data concerned single-drug additions to PD solution while 151 data were due to combined addition (two drugs). The stability results were summarised in a table. Conclusions: Adding antibiotics to PD solutions is essential for the treatment of peritonitis. Because of long exposure times, checking drug stability represents a crucial step to avoid underdosing or toxicity. Rapid access to the latest available stability data should help hospital pharmacists to manage intraperitoneal administration of drugs. No conflict of interest.